1999
DOI: 10.1210/jcem.84.8.5894
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Interleukin-6 Secretion and Quantity and Depth of Sleep

Abstract: Patients with pathologically increased daytime sleepiness and fatigue have elevated levels of circulating interleukin-6 (IL-6). The latter is an inflammatory cytokine, which causes sickness manifestations, including somnolence and fatigue, and activation of the hypothalamic-pituitary-adrenal axis. In this study, we examined: 1) the relation between serial measurements of plasma IL-6 and quantity and depth of sleep, evaluated by polysomnography; and 2) the effects of sleep deprivation on the nyctohemeral patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
205
4
7

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 395 publications
(223 citation statements)
references
References 14 publications
7
205
4
7
Order By: Relevance
“…Other researchers have demonstrated that higher plasma IL-6 levels are associated with adverse health habits: values are higher in smokers than nonsmokers, in individuals who report less physical activity, in those whose sleep is impaired, and in those with a higher BMI, all behaviors that are adversely affected by stress (14,34,37,(50)(51)(52). Although the linkage between caregiving and IL-6 was still significant in our data after accounting for these health behaviors, chronic stressors are also likely to affect IL-6 and thus health through these pathways as well.…”
Section: Resultsmentioning
confidence: 99%
“…Other researchers have demonstrated that higher plasma IL-6 levels are associated with adverse health habits: values are higher in smokers than nonsmokers, in individuals who report less physical activity, in those whose sleep is impaired, and in those with a higher BMI, all behaviors that are adversely affected by stress (14,34,37,(50)(51)(52). Although the linkage between caregiving and IL-6 was still significant in our data after accounting for these health behaviors, chronic stressors are also likely to affect IL-6 and thus health through these pathways as well.…”
Section: Resultsmentioning
confidence: 99%
“…Increased daytime plasma levels of IL-6 were also noted after sleep deprivation and in patients with excessive daytime sleepiness. 4,14,20 IL-6 is one of the key regulators of CRP synthesis by the liver. 5 The repetitive apneas during OSA induce not only hypoxemia, but also sleep fragmentation with consequent insufficient sleep and daytime somnolence.…”
Section: Shamsuzzaman Et Al Obstructive Sleep Apnea and C-reactive Prmentioning
confidence: 99%
“…Sleep deprivation also induces an increase in cytokines. 4,14 We tested the hypothesis that OSA patients have increased plasma CRP. …”
mentioning
confidence: 99%
“…However, in humans, acute peripheral administration of IL-6 reduces delta sleep in the first half of the night when circulating levels of IL-6 are elevated (Späth-Schwalbe et al 1998). Vgontzas and colleagues have further found that daytime elevations of circulating IL-6 are associated with severity of sleepiness and fatigue in sleep disordered patients (Vgontzas et al 1997), and that sleep deprivation leads to daytime over-secretion of IL-6 (Vgontzas et al 1999) in which daytime plasma levels of IL-6 negatively correlate with amounts of slow wave sleep. In view of this converging evidence, it is tempting to speculate about a link between cytokines and disordered sleep in the African-American alcoholics in which cytokine abnormalities contribute the severity of sleep disturbance in these patients.…”
Section: Alcoholism Sleep and Immunitymentioning
confidence: 96%